2021
DOI: 10.3390/rs13224562
|View full text |Cite
|
Sign up to set email alerts
|

Remote Sensing Detecting of Yellow Leaf Disease of Arecanut Based on UAV Multisource Sensors

Abstract: Unmanned aerial vehicle (UAV) remote sensing technology can be used for fast and efficient monitoring of plant diseases and pests, but these techniques are qualitative expressions of plant diseases. However, the yellow leaf disease of arecanut in Hainan Province is similar to a plague, with an incidence rate of up to 90% in severely affected areas, and a qualitative expression is not conducive to the assessment of its severity and yield. Additionally, there exists a clear correlation between the damage caused … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
24
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(25 citation statements)
references
References 48 publications
1
24
0
Order By: Relevance
“…For identification of agricultural pests and diseases, the visible red band, which is highly absorptive in green plants, and the nearinfrared band, which is highly reflective and transmissive in green plants, are often selected. The spectral response of these two bands to the same biophysical phenomena provides a strong contrast that changes with the leaf canopy structure and coverage; hence, their ratio, difference, or linear combination may be utilized to augment or disclose the implicit vegetation information (Lei et al, 2021). In the present study, the normalized difference vegetation index (NDVI), ratio vegetation index (RVI), physiological reflex vegetation index (PhRI), modified chlorophyll absorption ratio index (MCARI), transformed chlorophyll absorption ratio index (TCARI), and green index (GI) were chosen.…”
Section: Vegetation Indexmentioning
confidence: 99%
See 1 more Smart Citation
“…For identification of agricultural pests and diseases, the visible red band, which is highly absorptive in green plants, and the nearinfrared band, which is highly reflective and transmissive in green plants, are often selected. The spectral response of these two bands to the same biophysical phenomena provides a strong contrast that changes with the leaf canopy structure and coverage; hence, their ratio, difference, or linear combination may be utilized to augment or disclose the implicit vegetation information (Lei et al, 2021). In the present study, the normalized difference vegetation index (NDVI), ratio vegetation index (RVI), physiological reflex vegetation index (PhRI), modified chlorophyll absorption ratio index (MCARI), transformed chlorophyll absorption ratio index (TCARI), and green index (GI) were chosen.…”
Section: Vegetation Indexmentioning
confidence: 99%
“…UAV hyperspectral remote sensing facilitates information extraction in image and spectral dimensions, and is frequently employed for monitoring agricultural growth conditions, and pest and disease stress in the field. Photosynthesis is an essential reference for evaluation of plant development (Hunt et al, 2013, Sun Q. et al, 2021, and chlorophyll content is an indication of plant photosynthetic capacity; hence, chlorophyll content can effectively reflect the growth status of a crop (Ji et al, 2021;Kaivosoja et al, 2021;Lei et al, 2021). The variation of the chlorophyll content of crops is important for monitoring the growth of crops.…”
Section: Introductionmentioning
confidence: 99%
“…Implementation of Unmanned Aerial Vehicle (UAV) technology helps monitor plant health on plantations quickly, effectively, and efficiently [9]. Most of the studies identified canopy density based on the vegetation index on multispectral satellite images.…”
Section: Introductionmentioning
confidence: 99%
“…Kanan and Kumar [9] proposed the method where comparison between the data values are done by using a regression algorithm to find similarities in the pattern of conditions using IoT sensors. Lei et al [10] focused on using many machine learning algorithms like back propagation in neural network (BPNN), decision tree (DT), naive Bayes and k-nearest neighbors algorithm (KNN). A disease detection and classification system based on Android was proposed by Tlhobogang and Wannous [11].…”
Section: Introductionmentioning
confidence: 99%